Pengembangan Sistem Informasi Pendaftaran Tanah Sistematis Lengkap (PTSL) Kementerian Agraria dan Tata Ruang/BPN Kantor Pertanahan Kabupaten Malang - Nurul Ilmi Muhlisah Aziz; Ismiarta Aknuranda; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Pendaftaran Tanah Sistematis Lengkap (PTSL) is a program launched by the government through the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency which aims to ensure certainty and legal protection of citizens' land ownership. This program involves three parties, the applicants, the committee formed by villagers, and the local Regional Land Office (known as Kantah). PTSL procedure begins by recording the data of PTSL participants by the committee. After that the committee sends the nominative list of participants to the Malang District Land Office by bringing the required documents to be converted into land certificates. However, Malang Regency Land Office is often confronted with the problem of delays in the process of releasing land certificates because the documents collected by the applicant are often incomplete or inappropriate. Based on the problems that have been described, an information system is needed that is able to be an intermediary of the committee and Malang Regency Land Office in coordinating the PTSL application submitted by the applicants. This research applies the waterfall model. In the implementation phase, system applied Model-View-Controller pattern and CodeIgniter framework. The result of implementation phase is tested by applying validation testing and browser compatibility testing. The validation test results show valid results, while for browser compatibility testing there are 5% error issues and system can be run on several browsers.